Computer aided design of mechatronic systems - Mrozek, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
Any successful company must react quickly to changing trends in the market. New products should be designed and manufactured quicker and cheaper than counter partners do. A shorter design time provides a distinct competitive advantage. The paper describes two approaches towards designing interdisciplinary mechatronic systems: the first is visual modeling with the UML, the second is physical modelling with Modelica.
Keywords: mechatronics; UML; physical modelling; Modelica; Dymola; Simulink; Stateflow